Polish screenings of the russian novel (visual interpretations of novels of F.M. Dostoevsky Idiot and of M.a. Bulgakov Master and Margarita) - Galina Nefagina (Polilog: Studia Neofilologiczne, 2019)
Polish screenings of the russian novel (visual interpretations of novels of F.M. Dostoevsky Idiot and of M.a. Bulgakov Master and Margarita)